How to foster rural sustainability through farming workforce rejuvenation? Looking into involuntary newcomers' spatial (im)mobilities - Francisco Sim\~oes; Ilkay Unay-Gailhard; Alen Mujčinović; Bernardo Fernandes (Sustainability, 2021)
This conceptual paper aims to expand the notion of “farming newcomers” in Europe by also including those that we label “involuntary newcomers”, who correspond to the workforce coming unwillingly to farming for reasons associated with spatial (im)mobilities. We fully develop our aim in four steps. Firstly, we present an integrative literature review which describes how the interplay between the key concepts of the sustainable farming framework (i.e., sustained development, networked rural development, and spatial (im)mobilities) tailor the newcomers' arrival to the farming sector. Secondly, we define involuntary newcomers, describe their profiles and list the barriers to their engagement with sustainable farming. Thirdly, we advance some implications and limitations of our work for mobility research agendas. Fourthly, we conclude with an overview of the main inputs provided by our paper. We contribute to the literature by showing that: (a) newcomers must be defined beyond land ownership; (b) involuntary newcomers are very diverse, due to trends in spatial (im)mobilities; and (c) there is a high risk of the sustainable farming framework failing to meet its ambitions if it continues to ignore involuntary newcomers (and the barriers they encounter) in sustainable forms of agriculture.
Keywords: 630; newcomers; NEETs; migrants; rurality; farming; workforce; sustainability